PROMOSI SENI BUDAYA DAN KEARIFAN LOKAL WILAYAH KABUPATEN JEMBER MELALUI TELEVISI LOKAL - Hary Kresno Setiawan; Renta Vulkanita Hasan; A. Lilik Slamet Raharsono (LITERASI: Indonesian Journal of Humanities, 2013)
The invention and application of the media forms using satellite communications, such as telephone and television, as well as the technological transportation advances result in the fading of physical, spatial boundaries because information on all events occuring in any part of the world becomes easily accessible to many people in different places almost in no time. Mass media such as television, can be interpreted simply as one of the instruments which reinforces human efforts in realizing the above obsession. The optimization and promotion of indigenous arts and culture of the Jember regency in the form of documentation and the making of the album as one of the shows on television programmes can serve as representation and image creation of the area and its complicated culture. Through this study, it is expected to create a better communication between communities and cultures in the regency of Jember that can be utilized to help the local government in formulating policies to explore and to develop its potential resources.Keywords: promotion , arts, local wisdoms, Jember regency, local television